Configuring School and Community for Learning: the role of governance. (1st March 2004) - Ranson, Stewart
Abstract : The argument of the paper proposes that learning grows out of motivation which depends upon recognising and valuing the distinctive qualities of each and the cultural traditions they embody. If learning expresses a journey between worlds, the challenge for the school is to create a learning community that brings together local and cosmopolitan in its pedagogic practices. This configuration of the school and its communities, by interconnecting the symbolic orders of each, creates the conditions for relevance, motivation and learning. Excellent teachers have always sought, as a defining principle of their individual practice, to relate activities within their classroom to the interests of the child. But the argument being developed here proposes that this configuration is a strategic and systemic task for the governance of school as a whole institution.